Tectono-metamorphic history of the re-worked, high-grade Maud Belt at central-Eastern H.U. Sverdrupfjella, Antarctica - Byrnes, Gregory (Department of Geological Sciences, 2016)
The reworking of granulites by amphibolite- to granulite-facies metamorphism can complicate the interpretation of their geological history because the event that reached higher peak P-T conditions will either completely overprint earlier peak assemblages or prevent the formation of new 'peak' minerals. The extent of reworking in granulites is controlled by three main factors, namely: (1) the pressures and temperatures reached in earlier and later metamorphic events, (2) the extent of deformation during subsequent events, and (3) the amount of fluid influx into the system during subsequent metamorphic events. Extensive reworking will occur if the peak temperature of the later event exceeds that of the earlier event, but if it does not, reworking will be less pervasive, and restricted to areas of deformation and/or fluid influx. The Salknappen nunatak in central-Eastern H.U. Sverdrupfjella, Antarctica forms a part of the highgrade Maud Belt that was formed by a granulite facies Grenvillian orogeny and was variably overprinted by high-grade metamorphism (eclogite to amphibolite facies) during the PanAfrican orogeny. The degree of reworking during the Pan-African has been a contentious issue for some time, with early workers assigning the metamorphic peak to the Grenvillian, whereas others assigned it to the Pan-African. Mineral assemblages and textures preserved in metapelitic and metamafic rocks preserve evidence of only one prograde to retrograde metamorphic cycle with peak mineral assemblages that are characteristic of granulites. Sillimanite in metapelitic rocks forms pseudomorphs after kyanite whereas garnet breakdown microstructures and in both metapelitic and metamafic rocks formed as a result of near-isothermal decompression. Garnet and hornblende display retrograde zoning profiles whereas retrograde cummingtonite, hornblende, plagioclase and ilmenite in metamafic rocks moderately constrain retrograde conditions. Pseudosection modelling with THERMOCALC on peak mineral assemblages from metapelitic and metamafic samples collected at Salknappen provides a robust peak P-T estimate (M1) of 760 – 790 ºC at 8.5 – 10 kbar. Phase diagram modelling of more subtle retrograde assemblages constrain retrograde metamorphic conditions (M2) to between ~550 – 750 °C and ~2 – 5 kbar. Both M1 and M2 likely occurred during the Grenvillian in a single orogenic cycle along a clockwise metamorphic path, where peak metamorphism was followed by near-isothermal decompression of ~5 kbar. Recrystallised quartz in melt leucosomes confirms that retrogression (M2) occurred after peak metamorphism. M2 was followed by the intrusion of megacrystic leucogranite dykes that most likely formed during the Pan-African in response to iii melt migration as a result of melting deeper in the crust. These dykes and earlier gneisses were intruded by the Dalmation granites at c. 470 Ma, at which point the Salknappen nunatak was at crustal conditions approximating the brittle-ductile transition. The study area in central-Eastern H.U. Sverdrupfjella preserves the peak and retrograde metamorphic assemblages from the Grenvillian orogeny and does not display evidence of reworking by a later granulite facies event. Salknappen does not display evidence of reworking during the Pan-African because peak metamorphism did not exceed peak temperatures attained during the Grenvillian orogeny and also did not form discrete, localised deformation zones with a significant influx of fluid during the Pan-African orogeny. This study presents a case where the effects of mid-crustal reworking by a high-grade metamorphic event are not shown due to the lack of rehydration, pervasive deformation and an elevated residuum solidus as a result of higher peak temperatures in an earlier granulite facies metamorphic event. When working with polymetamorphic terranes that have been subjected to more than one granulite facies orogenic cycle, the interpretation of the geological history of such an area should be done with caution and P-T estimates should be done with methods that are less affected by the long retrograde histories.